Corporate Governance on Financial Report Timeliness among Quoted Non-financial Firms in Nigeria - Otiedhe, Gabriel Moses; Ofor, Nkechi Theresa; Okagbare, Kingley (Perkumpulan Dosen Muslim Indonesia, 2023)
The study seeks to examine the effect of corporate governance on financial report timeliness among quoted non-financial firms in Nigeria between the periods of 2013-2022. Specifically, there are twenty one (21) consumer goods firms and thirteen (13) industrial goods firms listed in the Nigerian Exchange Group as at 31st December, 2023 respectively. The study purposively selected ten (10) consumer goods firms and seven (7) industrial goods firms within the reviewed periods. The variables used to measure corporate governance are: board size (BBS), board composition (BOC), board expertise (BOP) and Board Gender Diversity (BGD) while regressed, and financial report timeliness (FRT). The Hausman test evidenced that, the random effect model is the most appropriate model for the study. The study reported that board size has a negative significant effect on financial report timeliness while has a positive insignificant effect on financial report timeliness (FRT). Both board gender diversity and board expertise have positive effect on financial report timeliness (FRT). Hence, board expertise and board gender diversity improves financial report timeliness. Consequently, shareholders of the sampled firms should to elect gender diverse boards that have the right balance between men and women.